2011
DOI: 10.1021/jp1109256
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Theoretical Study of Cleavage of the Glycosidic Bond of 2′-Deoxyadenosine: Base Excision-Repair Mechanism of DNA by MutY

Abstract: The enzyme adenine DNA glycosylase, also called MutY, is known to catalyze base excision repair by removal of adenine from the abnormal 2'-deoxyadenosine:8-oxo-2'-deoxyguanosine pair in DNA. The active site of the enzyme was considered to consist of a glutamic acid residue along with two water molecules. The relevant reaction mechanism involving different barrier energies was studied theoretically. Molecular geometries of the various molecules and complexes involved in the reaction, e.g., the reactant, interme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 73 publications
(145 reference statements)
2
31
0
Order By: Relevance
“…Further investigations into the transition state structure of MutY showed that the irreversible breakage of the N-glycosidic bond could not take place until a H 2 O atom was present and that the enzyme stabilized the excision site after excision (McCann and Berti, 2008). Recently, a two-step reaction was proposed to be the basis of the catalytic activity of MutY, as opposed to the three-step mechanism proposed before (Tiwari et al, 2011). …”
Section: Function Of Muty and Mutyhmentioning
confidence: 99%
“…Further investigations into the transition state structure of MutY showed that the irreversible breakage of the N-glycosidic bond could not take place until a H 2 O atom was present and that the enzyme stabilized the excision site after excision (McCann and Berti, 2008). Recently, a two-step reaction was proposed to be the basis of the catalytic activity of MutY, as opposed to the three-step mechanism proposed before (Tiwari et al, 2011). …”
Section: Function Of Muty and Mutyhmentioning
confidence: 99%
“…[37][38][39][40][41] Hotokka et al 37 studied hydrolysis of adenosine and the 3-methyladenosinium ion m 3 Ado + using semiempirical and Hartree-Fock ab initio calculations. Tiwari et al 41 examined N-glycosidic bond cleavage of dAdo induced by glutamic acid with two water molecules using quantum chemical methods. Their results suggested that N7 protonation better facilitates glycosidic bond hydrolysis than N1 and N3 protonation.…”
Section: Introductionmentioning
confidence: 99%
“…The amino acids are the building blocks of proteins and the protein synthesis is dictated by DNA structure. The interaction of the DNA bases with specific amino acids plays a crucial role in the repair of damaged DNA by proteins [3]. For example, the Ade-glutamic acid interaction is of great importance in the repair of damaged DNA by the protein MutY [3].…”
mentioning
confidence: 99%
“…The interaction of the DNA bases with specific amino acids plays a crucial role in the repair of damaged DNA by proteins [3]. For example, the Ade-glutamic acid interaction is of great importance in the repair of damaged DNA by the protein MutY [3]. In this regard, a thorough understanding of the interaction of nucleobases with amino acids is essential.…”
mentioning
confidence: 99%